Human Elimination of Phthalate Compounds: Blood, Urine, and Sweat (BUS) Study - Stephen J. Genuis; Sanjay Beesoon; Rebecca A. Lobo; Detlef Birkholz (The Scientific World Journal)
Background. Individual members of the phthalate family of chemical compounds are components of innumerable everyday consumer products, resulting in a high exposure scenario for some individuals and population groups. Multiple epidemiological studies have demonstrated statistically significant exposure-disease relationships involving phthalates and toxicological studies have shown estrogenic effects in vitro. Data is lacking in the medical literature, however, on effective means to facilitate phthalate excretion. Methods. Blood, urine, and sweat were collected from 20 individuals (10 healthy participants and 10 participants with assorted health problems) and analyzed for parent phthalate compounds as well as phthalate metabolites using high performance liquid chromatography-tandem mass spectrometry. Results. Some parent phthalates as well as their metabolites were excreted into sweat. All patients had MEHP (mono(2-ethylhexyl) phthalate) in their blood, sweat, and urine samples, suggesting widespread phthalate exposure. In several individuals, DEHP (di (2-ethylhexl) phthalate) was found in sweat but not in serum, suggesting the possibility of phthalate retention and bioaccumulation. On average, MEHP concentration in sweat was more than twice as high as urine levels. Conclusions. Induced perspiration may be useful to facilitate elimination of some potentially toxic phthalate compounds including DEHP and MEHP. Sweat analysis may be helpful in establishing the existence of accrued DEHP in the human body.